Burn size estimation: A remarkable history with clinical practice implications - Gretchen J. Carrougher; Tam N. Pham (Elsevier, 2024)
Determining the size of a burn injury is a critical metric in the care of the burn patient. Several long-standing methods exist to estimate burn size to include the Rule of Nines, Lund-Browder Chart, and Palmar method; all of which remain in clinical use today. Development and use of these metrics first began in the late 1800s. Understanding these clinical tools and others, with an appreciation of their development, limitations, and utility, is important for the competent burn care clinician today. This review provides an evolutional history for these metrics and use in clinical practice.